Solenopsora rhizomorpha (Catillariaceae): A new lichen species from India - Christy, Arun; Sequeira, Stephen; Anilkumar, Aswathi; Joseph, Siljo (Phytotaxa, 2024)
A new species of Solenopsora (Lichenized fungi), S. rhizomorpha from the Western Ghats biodiversity hotspot, India, is described and illustrated, along with its distribution map. The species is characterized by small foliose-type thallus covered with white pruina, presence of rhizines, and lacking secondary metabolites. In addition, the genus Solenopsora is recorded in India for the first time.